2006
DOI: 10.1007/s10620-006-3162-7
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Electrical Stimulation Regulates Colonic Transit Via the Nitrergic Pathway in Rats

Abstract: Gastrointestinal electrical stimulation has been proposed for the treatment of gastrointestinal motor disorders. However, little is known about potential roles of colonic electrical stimulation (CES). The aim of this study was to evaluate the effect and mechanism of CES on colonic transit in conscious rats. Male rats (N = 14) were equipped with a pair of colonic serosal electrodes for stimulation and a catheter in the colon. Colonic transit was assessed in four randomized sessions with or without CES and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…One of the previous studies reported a significant correlation between electrical stimulation-induced reduced gastric tone and reduced food intake in dogs. According to this, electrical stimulation of the gut that exerts an inhibitory effect on gastric tone (29) has potential for treating obesity [28,29,[31][32][33][34][35]. The findings of the current study suggest that stimulation location along the gut is not critical, so electrical stimulation may be performed based on the ease of implementation, such as convenience of surgery.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…One of the previous studies reported a significant correlation between electrical stimulation-induced reduced gastric tone and reduced food intake in dogs. According to this, electrical stimulation of the gut that exerts an inhibitory effect on gastric tone (29) has potential for treating obesity [28,29,[31][32][33][34][35]. The findings of the current study suggest that stimulation location along the gut is not critical, so electrical stimulation may be performed based on the ease of implementation, such as convenience of surgery.…”
Section: Discussionmentioning
confidence: 73%
“…Although most clinicians and researchers have focused on gastric electrical stimulation in recent years, stimulating other parts of the gut has also been explored . Long-pulse GES is composed of single repeated pulses at a certain frequency (10 cpm in the present study) with the pulse width in the order of milliseconds (300 ms in this study), and has been shown to induce gastric and rectal relaxation [17,20,25,28]. The current study was designed to investigate the effects of electrical stimulation of various parts of the gut on gastric tone and to determine: (1) if the effect of electrical stimulation on gastric tone is organ-specific, distancerelated, or both; (2) the most potent method of stimulation for gastric tone; (3) if the effect of ileal electrical stimulation on gastric tone is mediated through the nitrergic pathway.…”
Section: Discussionmentioning
confidence: 91%
“…In a canine study with sequential (multichannel) colonic electrical stimulation, propagated colonic contractions were generated, and the movement of colonic content was accelerated [68,69]. Similar acceleration of colonic transit also was noted in rats [70].…”
Section: Animal Studiesmentioning
confidence: 69%
“…After a nontoxic, nonabsorbable marker or dye is fed to the stomach, the movement of the substance can be detected by X-ray or spectrophotometry throughout transportation in the GI tract during the period of any time interval (114,117,285). Visualization techniques including video fluoroscopy and magnetic resonance imaging (MRI) have been used in clinical or experimental settings to visualize GI motility by detection of solid food labeled with tracer (62,202,295). These noninvasive methods are attractive as they can be combined with sensory or motor functional measurements.…”
Section: Techniques For Functional Assessmentsmentioning
confidence: 99%